2021
DOI: 10.3390/antiox10050682
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Attenuates Aortic Remodeling in Aortic Dissection Associating with Moderated Inflammation and Oxidative Stress through a NO-Dependent Pathway

Abstract: Aortic dissection (AD) is a highly lethal vascular disease characterized by separation of the constituent layers of the aortic wall. An increasing body of research indicates that inflammatory response and oxidative stress are implicated in vascular remodeling, which plays a key role in the development of AD. Hydrogen sulfide (H2S) has been found to protect against various types of cardiovascular disease, including myocardial infarction, arthrosclerosis, and hypertension. However, research on the effect of H2S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…ACTA2, is a smooth muscle actin, ranks first among the four algorithms. The mutation of ACTA2 is closely related to aortic dissection ( Cooper and Brown, 2017 ; van de Laar et al, 2019 ).The second key gene IL6, encodes a cytokine that functions in inflammation and the maturation of B cells, the inflammatory mechanism plays a key role in the development and progression of AD ( Lu et al, 2021 ).CTGF, is a Protein Coding gene, and has important pro-inflammatory and pro-fibrotic characteristic ( Morales et al, 2018 ), which play an important role in the progression of AD ( Bode-Jänisch et al, 2012 ; Bersi et al, 2017 ; Zhao and Bie, 2020 ). BGN, encodes a member of the small leucine-rich proteoglycan (SLRP) family of proteins, which plays a role in bone growth, muscle development and regeneration, and collagen fibril assembly in multiple tissues ( Fisher et al, 1991 ; Didangelos et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…ACTA2, is a smooth muscle actin, ranks first among the four algorithms. The mutation of ACTA2 is closely related to aortic dissection ( Cooper and Brown, 2017 ; van de Laar et al, 2019 ).The second key gene IL6, encodes a cytokine that functions in inflammation and the maturation of B cells, the inflammatory mechanism plays a key role in the development and progression of AD ( Lu et al, 2021 ).CTGF, is a Protein Coding gene, and has important pro-inflammatory and pro-fibrotic characteristic ( Morales et al, 2018 ), which play an important role in the progression of AD ( Bode-Jänisch et al, 2012 ; Bersi et al, 2017 ; Zhao and Bie, 2020 ). BGN, encodes a member of the small leucine-rich proteoglycan (SLRP) family of proteins, which plays a role in bone growth, muscle development and regeneration, and collagen fibril assembly in multiple tissues ( Fisher et al, 1991 ; Didangelos et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent report indicates that molecular pathways and indexes that regulate the transition of VSMC phenotype might impact the development of AD [ 26 ]. In eukaryocytes, the metabolism of phosphoinositol is the core of regulating cell homeostasis [ 27 ], among which PI3P family is one of the most abundant lipids and play a critical role in endocytosis and autophagosome membrane dynamics in cells [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data indicate that H 2 S improves diabetic endothelial dysfunction, 34 inhibits myocardial apoptosis after myocardial infarction, 35 and inhibits VSMC proliferation and migration induced by hyperglycaemia 27 ; recent data from our laboratory and others revealed that exogenous H 2 S attenuates angiotensin II (Ang II)–induced VSMC phenotypic switch and vascular remodeling. 12 , 36 However, there are no published literature on the potential effect of exogenous H 2 S on AF activation. Our study found that TGF-β1 induced AF phenotype switching, proliferation, and migration, which were ameliorated by exogenous H 2 S administration.…”
Section: Discussionmentioning
confidence: 99%